«Un nuovo tipo umano». Per un antropologia del lavoro industriale a partire da «Americanismo e Fordismo» - Redini, Veronica (International Gramsci Journal, 2023)
This article aims to show the relevance of Gramsci’s reflections presented in “Americanism and Fordism” in ethnographic practice and the anthropological analysis of contemporary industrial work. Starting from research on working conditions in Romania, the author analyzes work discipline and the discipline of sexual life, showing how capitalism proceeds at the level of the relationship between capital and labour and between the sphere of production and reproduction.